Symmetry breaking: an efficient structure design of nonfullerene acceptors to reduce the energy loss in organic solar cells. Issue 16 (18th April 2023) - Liu, Tianyi; Zheng, Hui; Yu, Xinyu; Shi, Shengwei; Zhou, Yinhua; Li, Zhong'an
Abstract : This perspective summarizes the recently encouraging progress of asymmetric fused ring electron acceptors and tries to show a picture of the relationship between the asymmetric molecular structure, energy loss and device performance. Abstract : In recent years, the innovative design of small-molecule non-fullerene acceptors (NFAs), in particular fused ring electron acceptors (FREAs), has greatly promoted the development of organic solar cells (OSCs), with PCEs higher than 19% to date. However, there is still a certain efficiency gap compared to inorganic and perovskite solar cells, mainly due to the large energy loss ( E loss ) in OSCs. Impressively, symmetry breaking of FREAs has recently emerged as an effective molecular design strategy to reduce the E loss to a remarkably low value of 0.44 eV. Thus, in this perspective, we carefully summarize the recently encouraging progress of asymmetric FREAs and try to show a picture of the relationship between the asymmetric molecular structure, E loss, and the device performance. Moreover, molecular insights for the future development of high performance asymmetric NFAs are also provided.